2023
DOI: 10.1002/adom.202202603
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Symmetry α‐MoO3 Heterostructures for Wave Plate Applications in Visible Frequencies

Abstract: Figure 5. Overlapping flakes: a) Schematic representation of the overlapping flakes along with the experimental setup. b) Photo of the overlapping flakes under study with marked regions I, II, and III representing respectively the bottom flake, top flake, and the overlapping region. c) The simulated and measured ratio of the cross-polarized to co-polarized transmittance for regions marked in (b) for flake rotation angle α = 68 ○ . The dashed line represents the case where there is no rotation between the flake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Using the reported refractive indices, we calculate the interference enhancement factors of SVPM and TVPM for α-MoO 3 with different thicknesses on the SiO 2 /Si substrate excited by 532 and 633 nm, as shown in Figure S5 (for more calculated details, please see Part 3 in the Supporting Information). Compared to BP and b-As, , the enhancement factors of α-MoO 3 vary less with thickness, which may be attributed to the low extinction coefficient and refractive indices (close to 2) of α-MoO 3 . , When the thickness of α-MoO 3 is less than 50 nm, the enhancement factors decrease (increase) with thickness under 532 (633) nm excitation. The variation of the I of α-MoO 3 with thickness is most likely attributed to the enhancement factor.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Using the reported refractive indices, we calculate the interference enhancement factors of SVPM and TVPM for α-MoO 3 with different thicknesses on the SiO 2 /Si substrate excited by 532 and 633 nm, as shown in Figure S5 (for more calculated details, please see Part 3 in the Supporting Information). Compared to BP and b-As, , the enhancement factors of α-MoO 3 vary less with thickness, which may be attributed to the low extinction coefficient and refractive indices (close to 2) of α-MoO 3 . , When the thickness of α-MoO 3 is less than 50 nm, the enhancement factors decrease (increase) with thickness under 532 (633) nm excitation. The variation of the I of α-MoO 3 with thickness is most likely attributed to the enhancement factor.…”
Section: Resultsmentioning
confidence: 91%
“…It is reported that Δn equals 0.15 (0.12) under 532 (633) nm excitation. 46 For the tBL α-MoO 3 samples (∼28.0 nm), ϕ ac 532 = ∼2.84°and ϕ ac 633 = ∼1.91°. Such a small ϕ ac guarantees that the birefringence modulation is weak and can be ignored.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The birefringence values for the P4/nmm phase of the system, as estimated from SCF (nSCF) calculation are found to be ∼1.99 (1.53), 2.03 (1.42) and 1.83 (1.15) at E M ∼ 1.8, 2 and 2.5 eV respectively. The high n D values for the above referred phase of the compound in the visible region of the EM wave (1.7 < E M < 3 eV) may be helpful in designing enhanced optoelectronic devices such as polarizing prisms, optic-axis gratings, light modulators and polaroids [94,[119][120][121][122].…”
Section: Imaginary Part Of Complex Dielectric Functionmentioning
confidence: 99%